Analysis of the Revitalization of the Trade Office in the Development of the Mampang Mandailing Natal Market - Rifki Akmal Tanjung; Wahyu Syarvina (Penerbit Jurnal Indonesia, 2022)
It is important to implement the traditional market revitalization policy, because it is well known that there is unfair competition between traditional and modern markets. This policy was successfully implemented, one of which was at the Mompang Mandailing Natal Market. This study aims to identify, analyze and describe the pattern of cooperation between actors in the revitalization of traditional markets at the Mompang Mandailing Natal Market in the perspective of good governance and what efforts are taken in the revitalization of traditional markets at the Mompang Mandailing Natal Market. This study uses a qualitative descriptive research method. The collaboration that has been carried out can be said to be going well which can be measured from the four principles of good governance, including accountability, participation, predictability (rule of law), and transparency. The efforts that have been taken consist of physical aspects (development and repair of market facilities) and non-physical aspects (guidance and empowerment of human resources).